Social Investment for Facing Migration Crisis - Meléndez Aguilar, Kristobal Miguel (European Journal of Sustainable Development, 2017)
The new immigration policy of the United States could intensify deportations of undocumented migrants with an economic, social and political effect in Mexico. This problem could generate economic, political and social instability in some Mexican states then it is relevant to study how to diminish this effect. Social investment could reduce the impact of this situation and could reduce the reasons for those Mexicans that want to migrate. Social investment focuses on considering the migrant as an asset that could be incorporated into the labor market with government programs that stimulate intensive labor public investment, reduced violence, training and increased wages. By using multiple linear regressions and descriptive statistics, it is shown that the levels of education, economic growth, poverty, labor purchasing power, violence and unemployment have an effect on Mexican migration levels. In this way, it is shown that it is possible to reverse this problem with positive impacts on the Mexican economy. Keywords: Migration, Social Investment, Intensive labor investment, Local income, Sustainable economic growth